Endogenous inspired biomineral-installed hyaluronan nanoparticles as pH-responsive carrier of methotrexate for rheumatoid arthritis - Alam, Md. Mahmudul; Han, Hwa Seung; Sung, Shijin; Kang, Jin Hee; Sa, Keum Hee; Al Faruque, Hasan; Hong, Jungwan; Nam, Eon Jeong; Kim, In San; Park, Jae Hyung; Kang, Young Mo (ELSEVIER SCIENCE BV, 2017)
Methotrexate (MTX), an anchor drug for rheumatoid arthritis (RA), has been suffered from refractoriness and high toxicity limiting effective dosage. To mitigate these challenges, the ability to selectively deliver MTX to arthritis tissue is a much sought-after modality for the treatment of RA. In this study, we prepared mineralized nanoparticles (MP-HANPs), composed of PEGylated hyaluronic acid (P-HA) as the hydrophilic shell, 5 beta-cholanic acid as the hydrophobic core, and calciumphosphate (CaP) as the pH-responsivemineral. Owing to the presence of CaP as the diffusion barrier, mineralized HANPs revealed the pH-responsiveness of release kinetics of MTX across neutral to acidic conditions. HANPs were internalized via receptor-mediated endocytosis in macrophages which involvedmolecular redundancy amongmajor hyaladherins, including CD44, stabilin-2, and RHAMM. Following endocytosis, MP-HANPs loaded with doxorubicin revealed pH-dependent demineralization followed by dramatic acceleration of drug release into the cytosol compared to other HANPs. Furthermore, an in vivo study showed a significantly high paw-to-liver ratio of fluorescent intensity after systemic administration of MPHANP-Cy5.5, indicating improved biodistribution of nanoparticles into arthritic paws in collagen-induced arthritis mice. Treatment with MTX-loaded MP-HANPs ameliorated inflammatory arthritis with remarkable safety at high dose of MTX. We highlight the distinct advantages of combining key benefits of biomineralization and PEGylation with HA-based nanoparticles for arthritis-selective targeting, thus suggestingMP-HANPs as a promising carrier of MTX for treatment of RA. (C) 2017 Elsevier B. V. All rights reserved.
Keywords: MODIFYING ANTIRHEUMATIC DRUGS; CANCER-THERAPY; INTRACELLULAR DELIVERY; ACID NANOPARTICLES; NANOCARRIERS; TUMOR; RECEPTOR; DISEASE; OPPORTUNITIES; ARCHITECTURE